Fiscal foundations of inflation: Imperfect knowledge - Stefano Eusepi; Bruce Preston (Federal Reserve Bank of New York, 2013)
This paper proposes a theory of the fiscal foundations of inflation based on imperfect knowledge and learning. The theory is similar in spirit to, but distinct from, unpleasant monetarist arithmetic and the fiscal theory of the price level. Because the assumption of imperfect knowledge breaks Ricardian equivalence, details of fiscal policy, such as the average scale and composition of the public debt, matter for inflation. As a result, fiscal policy constrains the efficacy of monetary policy. Heavily indebted economies with debt maturity structures observed in many countries require aggressive monetary policy to anchor inflation expectations. The model predicts that the Great Moderation period would not have been so moderate had fiscal policy been characterized by a scale and composition of public debt now witnessed in some advanced economies in the aftermath of the 2007-09 global recession.
Keywords: E32; D83; D84; 330; debt management policy; maturity structure; monetary policy; expectations stabilization; Great Moderation